PROSES PENGAMBILAN KEPUTUSAN UNTUK PENENTUAN KEGIATAN BRANDING PT TELKOMSEL AREA MADURA - Anis Kurli; Ida Syafriyani; Ahmed David Anugerah; Lily Elserisa; M. Harun Rasyid Ridlo; Rachmad Rizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2022)
Abstract The decision-making process the branding activities of PT Telkomsel Area Madura is an important agenda that the company needs to pay attention to in balancing the development of competitors in the market. Branding as a product education media is an extension of the company to get closer to its consumers so that product knowledge is more detailed and open. This research aims to determine the decision-making process carried out by the company to determine the branding activities that will be carried out. The method used in this research is descriptive qualitative, namely the researcher tries to describe the decision-making process carried out by PT Telkomsel Area Madura in determining product branding activities on outdoor media and outlets/retailers. The results of the research on the decision-making process for determining the company's branding activities are: first, in a top-down manner related to branding activities in outdoor media based on the results of product assessments carried out by leaders in each region. Second, bottom-up related to branding activities at outlets/retailers based on market share results and sales data obtained from the marketing team in the field, these results are used as input to superiors in making branding decisions at each outlet/retailer. Keywords: Decision Making Process, Branding, and Products